Low-GWP refrigerants flow boiling heat transfer in a 5 PPI copper foam. (November 2015) - Diani, Andrea; Mancin, Simone; Doretti, Luca; Rossetto, Luisa
Highlights: The flow boiling heat transfer of R1234yf and R1234ze(E) inside a horizontal 5 PPI copper foam is studied. The two-phase heat transfer coefficients and pressure drops of two HFO refrigerants are measured. These new low-GWP refrigerants are compared against the more traditional R134a. The two-phase flow patterns inside the foam are presented and discussed. Abstract: This paper reports an experimental investigation of the heat transfer performance of the new low-GWP refrigerants, R1234yf and R1234ze(E), during flow boiling heat transfer inside a horizontal high porosity copper foam with 5 Pores Per Inch (PPI). Metal foams are a class of cellular structured materials consisting of a stochastic distribution of interconnected pores; these materials have been proposed as effective solutions for heat transfer enhancement during both single and two-phase heat transfer. R1234yf and R1234ze(E) refrigerants are appealing alternatives of the more traditional R134a by virtue of their negligible values of GWP and normal boiling temperatures close to that of R134a, which make them suitable solution in several different applications, such as: refrigeration and air conditioning and electronic thermal management. This work compares the two-phase heat transfer behaviour of these new HFO refrigerants, studying the boiling process inside a porous medium and permitting to understand their effective heat transfer capabilities. The experimental measurements were carried out by imposing three different heat fluxes: 50, 75, and 100 kW m −2, at a constant saturation temperature of 30 °C; the refrigerant mass velocity was varied between 50 and 200 kg m −2 s −1, whilst the mean vapour quality varied from 0.2 to 0.95. The two-phase heat transfer and pressure drop performance of the two new HFO refrigerants is compared against that of the more traditional R134a.